2018
DOI: 10.1002/lno.11063
|View full text |Cite
|
Sign up to set email alerts
|

Wave and tide‐driven flow act on multiple scales to shape the distribution of a juvenile fish (Albula vulpes) in shallow nearshore habitats

Abstract: Environmental stress associated with incident flow is among the most fundamental physical factors structuring fish distributions. In shallow marine habitats, flow‐related stress arises through several distinct processes, yet their combined ramifications for habitat utilization by fishes are rarely evaluated concurrently. We used hydrodynamic models to resolve spatial and temporal variability in wave‐ and tide‐driven water velocities across the littoral zone of a subtropical island, and related these, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 138 publications
0
6
0
Order By: Relevance
“…As with Atlantic tarpon, inclusion of nursery habitat requirements for common snook should be incorporated into management strategies in coming decades, including mitigation measures tied to the physiochemical changes predicted through climate change. However, bonefish ( A. vulpes ) depend on low energy sandy habitats for larval settlement (Haak et al 2019 ), and such habitats are not expected to extend northward along the Florida coastline in the face of climate change and other anthropogenic disturbances. Thus, even with the potential for long distance larval transport that can provide connections among the adult populations and drive local population dynamics (Zeng et al 2019 ), other limitations may constrain the capacity of bonefish to contend with the impacts of climate change.…”
Section: Knowledge Gaps and Calls To Actionmentioning
confidence: 99%
“…As with Atlantic tarpon, inclusion of nursery habitat requirements for common snook should be incorporated into management strategies in coming decades, including mitigation measures tied to the physiochemical changes predicted through climate change. However, bonefish ( A. vulpes ) depend on low energy sandy habitats for larval settlement (Haak et al 2019 ), and such habitats are not expected to extend northward along the Florida coastline in the face of climate change and other anthropogenic disturbances. Thus, even with the potential for long distance larval transport that can provide connections among the adult populations and drive local population dynamics (Zeng et al 2019 ), other limitations may constrain the capacity of bonefish to contend with the impacts of climate change.…”
Section: Knowledge Gaps and Calls To Actionmentioning
confidence: 99%
“…The viability of these connections is dependent upon the environments in which larvae settle, as habitats are not always suitable for a given life stage, disrupting the completion of connectivity (i.e., next generation spawning) [ 103 ]. We did not discriminate against shoreline composition, which can preclude larval settlement, especially for bonefish that require softly sloping sandy shorelines with low energy littoral zones [ 104 ]. Settlement positions within the LDMs are not necessarily definitive given that bonefish, like other fish [ 85 , 105 , 106 ], are likely to exhibit some capacity of spatiotemporal control during settlement to select for compatible nursery habitat.…”
Section: Discussionmentioning
confidence: 99%
“…On Eleuthera, LDM larvae settled along the northern and eastern shoreline, while few larvae settle upon the leeward shores. Rigorous sampling for juvenile bonefish has only been conducted on Eleuthera, and efforts support prevailing transport to the windward side of Eleuthera where protected embayments contain nursery habitat [ 104 ]; however, CPUE of juvenile bonefish were comparatively higher at leeward stations within Rock Sound. Larvae in the 2018 suite of LDMs did reach Rock Sound in higher relative abundances than the windward embayments, though arrival to settlement habitat preceded the lower end of the settlement competency period (see Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For smaller specimens (<150 mm TL), a representative subsample of up to 30 individuals of each taxon was retained from a subset of seine hauls and sacrificed to permit more precise identification and measurement. Additional details on sampling methodology and the study area can be found in Haak et al (2019).…”
Section: Data Collectionmentioning
confidence: 99%
“…Environmental covariates.-To accommodate the diversity of fishes collected, and the likelihood that species with varying ecologies and functional roles may be influenced by distinct environmental factors, we considered an extensive array of independent predictors quantifying variation in biotic and abiotic habitat characteristics over a range of scales. Physical covariates included basic parameters such as water temperature and depth, as well as several measures of flow-related environmental stress arising because of incident waves and tidal currents, obtained from hydrodynamic models as outlined in Haak et al (2019). Biological predictors reflected both microhabitat characteristics and the arrangement of the broader seascape, comprising the coverage of benthic vegetation within the sampled area and its proximity to adjacent mangrove and coral reef habitats.…”
Section: Data Collectionmentioning
confidence: 99%